Centenarians as a model to discover genetic and epigenetic signatures of healthy ageing. (September 2018) - Puca, Annibale Alessandro; Spinelli, Chiara; Accardi, Giulia; Villa, Francesco; Caruso, Calogero
Highlights: Summary of interactions between genes and environment in longevity. Description of cellular mechanisms involved in longevity. Depiction of known epigenetics signatures of healthy aging. Abstract: Centenarians are a model of successful ageing. The data favours the theory that, in order to live to 100, it is mandatory to inherit the right genetic variants from parents or acquire epigenetic variants through the environment. Therefore, the study of epigenetic signatures of healthy ageing is becoming an important aspect to identify the role of chromatin modification in ageing and understand how manage this fine-tuning system. So, according to the concept of developmental plasticity, establishment of a longevity phenotype requires a combination of stochastic and non-stochastic events that modulate the genetic substrate and leads to a different outcome. It can be concluded that centenarians have a more powerful "engine" shaped by evolution, and that the environment, through epigenetic system, is a component influencing outcome.